2013
DOI: 10.3109/10717544.2012.762435
|View full text |Cite
|
Sign up to set email alerts
|

Faster absorption and higher systemic bioavailability of intranasal fentanyl spray compared to oral transmucosal fentanyl citrate in healthy subjects

Abstract: Context: Intranasal fentanyl spray (INFS) was developed for the treatment of breakthrough pain in cancer patients using an alternative route of administration. Objective: The aim of this clinical study was to investigate the pharmacokinetic (PK) profile and bioavailability of INFS in healthy subjects compared to oral transmucosal fentanyl citrate (OTFC). Materials and methods: In a randomized, single-center, open-label, two-way crossover PK study, 24 subjects (12 male, 12 female, mean age 25.2 years) received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…The doses of fentanyl used in the current study generated clinically relevant serum fentanyl concentrations in the range of 5-30 ng/ml. In humans, therapeutic serum concentrations of fentanyl show a C max ranging from 0.2 to 0.9 ng/ml after sublingual, intranasal, transmucosal fentanyl, or intravenous administration of fentanyl (Nave et al, 2013;Parikh et al, 2013), whereas unintentional overdose of transdermal patches show fentanyl blood concentrations ranging from 5 to 28 ng/ml (Jumbelic, 2010) and respiratory depression at plasma concentrations of 2.5-6.3 ng/ml in humans (Mildh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The doses of fentanyl used in the current study generated clinically relevant serum fentanyl concentrations in the range of 5-30 ng/ml. In humans, therapeutic serum concentrations of fentanyl show a C max ranging from 0.2 to 0.9 ng/ml after sublingual, intranasal, transmucosal fentanyl, or intravenous administration of fentanyl (Nave et al, 2013;Parikh et al, 2013), whereas unintentional overdose of transdermal patches show fentanyl blood concentrations ranging from 5 to 28 ng/ml (Jumbelic, 2010) and respiratory depression at plasma concentrations of 2.5-6.3 ng/ml in humans (Mildh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although intranasal delivery of drugs is directly targeted to the CNS, it has been reported that this type of drug administration results in significantly higher bioavailability and higher plasma drug levels than the oral pathway. [24][25][26] In this study, we explored whether intranasal administration of FSD-C10 could modulate systemic immune responses in EAE mice. As shown in Fig.…”
Section: Intranasal Fsd-c10 Modulates Systemic Immune Responses In Eaementioning
confidence: 99%
“…[24][25][26] In this study, we explored whether intranasal administration of FSD-C10 could modulate systemic immune responses in EAE mice. As shown in Fig.…”
Section: Intranasal Fsd-c10 Modulates Systemic Immune Responses In Eaementioning
confidence: 99%
“…[39][40][41][42][43] Dose proportionality has been observed that suggest linear pharmacokinetics. 39,41 Intranasal fentanyl possesses high bioavailability (F = 0.89) and is rapidly absorbed, with T max being 12-15 minutes.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…[39][40][41] After single-dose administration ranging from 75 to 200 μg, C max have been 0.7-1.7 ng/mL across studies. 39,[41][42][43][44] In cancer patients, elimination halflife (mean ± SD) was 193 ± 106, 255 ± 190, and 209 ± 79 minutes for a single dose of 50, 100, and 200 μg, respectively. 41 In comparison with another study in a different patient population, elimination half-lives of 89-279 minutes at doses of 75, 100, 150, and 200 μg have been reported.…”
Section: Pharmacokineticsmentioning
confidence: 99%